Healing the hospital environment : design, management and maintenance of healthcare premises - Hosking, Sarah (E & FN Spon, 1999)
This is an accessible guide to healthcare premises interior and exterior design and refurbishment for the non-specialist with practical advice and lists of UK organisations and suppliers for specialist advice, materials and funds.